Walking el Camino de Santiago (III) (Journal of Parents and Teachers, 2013)
This is the first article of a series of three of them that wants to show the essential part of the Camino de Santiago. It offers a description, insisting on the architectonic and cultural value of Santiago de Compostela and the end to Fisterra. The article is completed with a didactic guide.
Keywords: Camino de Santiago; art; Spain; cultural heritage; didactic material; activities.